2020
DOI: 10.3390/polym12071480
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Furan–Matrix Composites Blended with Modified Hollow Glass Microsphere

Abstract: In this study, a new class of thermal insulation composites was prepared by blending a modified hollow glass microsphere (HGM) with furan resin. The particle dispersion between the microparticles and resin matrix was improved using 3-methacryloxypropyltrimethoxy silane (KH-570). Furthermore, the structure and morphology of the modified HGM were characterised by Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM). In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The mechanical properties, chemical and thermal stabilities, thermal conductivity and flame retardancy can be tuned by the addition of an organically modified woven glass fiber and talc filler 368 or organically modified glass microspheres. 369 Fully bio-based composites can be prepared by furan resin copolymerization with tung oil and bacterial cellulose fibers 370 or by compression forming with bamboo culms, resulting in construction materials with a remarkable compressive strength and excellent recovery characteristics. 371 The reinforcement of FAlc resin with the melamine foam leads to a composite suitable for use as a highly efficient absorbent for oil–water separation due to its excellent sorption capacities for various oils and organic solvents and high recycling abilities.…”
Section: Branched Typementioning
confidence: 99%
“…The mechanical properties, chemical and thermal stabilities, thermal conductivity and flame retardancy can be tuned by the addition of an organically modified woven glass fiber and talc filler 368 or organically modified glass microspheres. 369 Fully bio-based composites can be prepared by furan resin copolymerization with tung oil and bacterial cellulose fibers 370 or by compression forming with bamboo culms, resulting in construction materials with a remarkable compressive strength and excellent recovery characteristics. 371 The reinforcement of FAlc resin with the melamine foam leads to a composite suitable for use as a highly efficient absorbent for oil–water separation due to its excellent sorption capacities for various oils and organic solvents and high recycling abilities.…”
Section: Branched Typementioning
confidence: 99%
“…Phenolic resins from biomasses have been indeed developed and studied extensively in recent decades, but the search for biobased alternative to standard phenolic in the specific sector of high charring matrices is still ongoing (Loganathan et al, 2021), even though it is predictable that the properties of resin synthesized from bioresources are lower than the raw material derived from oil (Ipakchi et al, 2020;Ma et al, 2020;Guo et al, 2021;Gruber et al, 2021). One example of nanofiller reinforced phenolic composites for ablative purposes comes from the paper of Ma et al, where the authors found that the addition of graphene oxide or graphitic carbon nitride (Figure 8C) (Ma et al, 2019) increased the char yield graphitization level during ablation, helping heat dissipation and thereby increasing the ablation resistance.…”
Section: Phenolicsmentioning
confidence: 99%
“…Currently, silane coupling agents containing both silicone functional groups and organic functional groups are widely used for such purposes. [12][13][14][15][16][17][18][19] Polypropylene (PP) is one of the most commonly used thermoplastic resins. Although pure PP can be used as thermal insulation and sound insulation materials, the mechanical properties are not sufficiently high for many applications.…”
Section: Introductionmentioning
confidence: 99%